Peckish : suggestions for the sophisticated snacker - Lenzer, Suzanne (Rodale, 2025)
"Mindful snacking is the philosophy that food stylist and prolific author Suzanne Lenzer lives by. Who doesn't love standing in front of a full fridge wondering what to pull out for a covert snack? Thoughtful snacking is also about moving beyond boards and platters when we entertain by adding dimension to the table, both in what we serve and how we serve it. Peckish is divided into charming chapters sorted by vessel such as On Toast, In Jars, Skewers & Sticks, In Bowls, and even the helpful Napkins Only so that the home cook can plan their snacking night with ease whether they're eating for one or entertaining a group of friends"--